Colonic microflora and plasma metabolite-based comparative analysis of unilateral ureteral obstruction-induced chronic kidney disease after treatment with the Chinese medicine FuZhengHuaYuJiangZhuTongLuo and AST-120 - Ziwei Chen; Shaobo Wu; Li Huang; Jing Li; Xueying Li; Yu Zeng; Zejun Chen; Ming Chen (Heliyon, 2024)
Background: Many researchers have investigated the use of Chinese herbs to delay the progression of chronic kidney disease (CKD) through their effects on colonic microflora and microbiota-derived metabolites. However, whether FuZhengHuaYuJiangZhuTongLuo (FZHY) has effects that are similar to those of AST-120 on CKD needs to be elucidated. Methods: In this study, we compared the effects of FZHY and AST-120 on the colonic microbiota and plasma metabolites in the CKD rat model. We developed a unilateral ureteral obstruction (UUO)-induced CKD rat model and then administered FZHY and AST-120 to these model rats. Non-targeted metabolomic LC-MS analysis, 16S rRNA sequencing, and histopathological staining were performed on plasma, stool, and kidney tissues, respectively, and the joint correlation between biomarkers and metabolites of candidate bacteria was analyzed. Results: Our results showed that administering FZHY and AST-120 effectively ameliorated UUO-induced abnormal renal function and renal fibrosis and regulated the composition of microbiota and metabolites. Compared to the UUO model group, the p_Firmicutes and o_Peptostreptococcales_Tissierellales were increased, while 14 negative ion metabolites were upregulated and 21 were downregulated after FZHY treatment. Additionally, 40 positive ion metabolites were upregulated and 63 were downregulated. On the other hand, AST-120 treatment resulted in an increase in the levels of g_Prevotellaceae_NK3B31_group and f_Prevotellaceae, as well as 12 upregulated and 23 downregulated negative ion metabolites and 56 upregulated and 63 downregulated positive ion metabolites. Besides, FZHY increased the levels of candidate bacterial biomarkers that were found to be negatively correlated with some poisonous metabolites, such as 4-hydroxyretinoic acid, and positively correlated with beneficial metabolites, such as l-arginine. AST-120 increased the levels of candidate bacterial biomarkers that were negatively correlated with some toxic metabolites, such as glycoursodeoxycholic acid, 4-ethylphenol, and indole-3-acetic acid. Conclusion: FZHY and AST-120 effectively reduced kidney damage, in which, the recovery of some dysregulated bacteria and metabolites are probably involved. As their mechanisms of regulation were different, FZHY might play a complementary role to AST-120 in treating CKD.